Model-dependent pharmacokinetic analysis of enalapril administered to healthy adult volunteers using orodispersible minitablets for use in pediatrics - Faisal M; Cawello W; Burckhardt BB; Laer S (Dove Medical Press, 2019)
Muhammad Faisal,* Willi Cawello,* Bjoern B Burckhardt, Stephanie Laer On behalf of LENA Consortium Institute of Clinical Pharmacy and Pharmacotherapy, Heinrich-Heine-University Düsseldorf, Düsseldorf, Germany *These authors contributed equally to this work Introduction: Comparative pharmacokinetic (PK) data analysis of drugs administered using developed child-appropriate and market authorized dosage formulation is sparse and is important in pediatric drug development. Objectives: To compare and evaluate any differences in PK of enalapril administered using two treatments of child-appropriate orodispersible minitablets (ODMTs) and market authorized reference tablet formulation (Renitec®) using PK compartment model and validated least square minimization method (LSMM) of parameter estimation. Methods: Full profile data sets were obtained from a phase I clinical trial, whereby three treatments of enalapril, ie, reference tablets with 240 mL water (treatment A), child-appropriate ODMTs with 240 mL (treatment B), and ODMTs dispersed in the mouth with 20 mL water (treatment C), were administered to 24 healthy adult volunteers. Virtual validation analysis was conducted using R program to select accurate and precise LSMM of parameter estimation. For the selection of PK model and estimation of parameters, enalapril data were fitted with one- and two-compartment models with first order of absorption and elimination, with and without incorporated lag time parameter (tlag). The log-transformed PK parameters were statistically compared by the two-sided paired t-test with the level of significance of P<0.05. Results: One-compartment model with first-order absorption and elimination and incorporated lag time adequately predicted concentrations of enalapril. Reciprocal of predicted concentration using iteratively reweighted LSMM was selected as the most appropriate method of parameter estimation. Comparison of PK parameters including rate constant of absorption and elimination, volume of distribution, and tlag between the three treatments showed significant difference (P=0.018) in tlag between treatments B and A only. Conclusion: Compared with reference formulation, enalapril administered from child-appropriate ODMTs administered with 240 mL water appeared 4 minutes earlier in serum. No other differences were observed in absorption, elimination, and relative bioavailability of drug between the three treatment arms. Keywords: enalapril, orodispersible minitablets, least square minimization method, child-appropriate dosage forms, model-dependent pharmacokinetics